Efektivitas Program Bantuan Stimulan Perumahan Swadaya (BSPS) Dalam Mendorong Dan Mningkatkan Inisiatif Keswadayaan Masyarakat Di Kecamatan Tambaksari Untuk Memperbaiki Rumah Tak Layak Huni - Febrihana, Pramudita; Sishadiyati, Sishadiyati; Priana, Wiwin (Peneliti.net, 2023)
The Swadaya Housing Stimulant Program (BSPS) is a government assistance effort aimed at low-income communities (MBR) supported by assistance recipients in order to increase access to adequate, safe, healthy, and comfortable housing and housing. Low-income (MBR) communities with bought power thus need government backing to have the ability to improve their homes from uninhabitable to habitable conditions such as building resilience, large Spaces, adequate sanitation access, and access to adequate drinking water. The study aims to identify the strength of as many as 65 beneficiaries of assistance in the surabaya city tamales. The method used in this study is a qualitative method with a descriptive type of research. Data sources in research are obtained through observation, field notebooks, and documentation. Based on research already done, results indicate that the majority of those receiving assistance from tambake-off services participated in money transfers to supplement materials purchase and labor costs. Then, followed by a swadaya form of carpentry performed by the families of the recipients in the construction of his life.